Biological Rationale for the Use of PPARγ Agonists in Glioblastoma - Ellis, Hayley P.; Kurian, Kathreena M. (Frontiers in Oncology, 2014)
Glioblastoma Multiforme (GBM) is the most common primary intrinsic CNS tumour and has an extremely poor overall survival, despite advances in neurosurgery, chemotherapy and radiation therapy. There has been interesting preliminary evidence suggesting that patients receiving the group of anti-diabetic drugs known as PPARγ (Peroxisome proliferator-activated receptor gamma) agonists have a lower incidence of glioma. The nuclear hormone receptor PPARγ has been found to be expressed in high grade gliomas, and its activation has been shown to have several antineoplastic effects on human and rat glioma cell lines, and in some instances an additional protective increase in antioxidant enzymes has been observed in normal astrocytes. At present, no clinical trials are underway with regards to treating glioma patients using PPARγ agonists, as Pioglitazone and Rosiglitazone are only FDA-approved for use in treatment of type-2 diabetes. This review presents the case for evaluating the potential of PPARγ agonists as novel adjuvants in the treatment of high grade glioma. We introduce the PPARγ pathway, PPARγ gene and its products and examine recent research in glioblastoma.